Overview Of The Condition Of The Dock Facilities At Kuala Tungkal Ferry Port - Kodrat Alam; Ferdinand Pusriansyah; Fajar Shiddiq (IWJ : Inland Waterways Journal, 2022)
Kuala Tungkal crossing port is a crossing Port located in Tanjung Jabung Barat regency, Jambi province, with crossings Kuala Tungkal - Dabo Singkep and Kuala Tungkal - Telaga Punggur. The port is operated by the Department of transportation of West Tanjung Jabung regency and supervised by BPTD Region V Jambi province. The condition of the facilities at the port is very important to review and make periodic repairs so as not to interfere with port operations. This study aims to determine the condition of the dock facilities in the form of fenders, Bolders, catwalks and various efforts to solve problems related to the condition of the dock facilities in accordance with the provisions. The method of analysis used in the form of observation, measurement of the dimensions of facilities and tides as well as, interviews to the ship operator. Based on the results it can be concluded that the condition of the dock facilities in a damaged condition and the absence of repair and maintenance of the port operator. Thus, it is necessary to plan the dock facilities in accordance with the needs and periodic maintenance so that the dock facilities are always durable.